ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN INTELLECTUAL CAPITAL PADA PROSPEKTUS IPO - Gea Randu Septiana; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the factors influencing the disclosure of intellectual capital (IC) information in the initial public offering (IPO) prospectuses in Indonesia. The analysis used independent variable of board size, board independence, board diversity, size, age, leverage, underwriter, auditor and offering stock. The dependent variable is intellectual capital (IC) disclosure index in IPO prospectuses.The study population is companies that IPO in Bursa Efek Indonesia (BEI/ Indonesia Exchange Stock) between 2008 and 2011. The sample used in this research was the secondary data from Bursa Efek Indonesia (BEI/ Indonesia Exchange Stock), i.e the prospectus of IPO company between 2008 and 2011. The sample was taken using the method of purposing sampling, and those meeting the selection criteria were also taken. The sample usedwas of 72 companies. The statistic method used was multiplied analysis linear regression, with hypotheses testing of statistic t and F tests. The extent of the intellectual capital (IC) disclosure index is quantified using content analysis methodology. The results provide evidence that board size, and auditor significantly influence the extent of IC disclosure in an IPO prospectus. Nonetheless, six variables, board independence, board diversity, size, age, leverage, underwriter and offering stock were not significant to the intellectual capital disclosure in an IPO prospectus.